(untitled) (Eurasian Research Bulletin, 2023)
The work is devoted to a review of the options for the use of collagen and collagenbased materials in medicine and the pharmaceutical industry. The problem of effective impact on the local manifestation of the wound process and at the present stage of development of medicine remains unresolved, despite the emergence of various drugs and techniques. Among the many types of cells that can have a clinical effect, dermal fibroblasts are of particular interest, which are a heterogeneous population of cells of the mesenchymal series and play a key role in the processes of regulating cellular interactions and maintaining skin homeostasis. Currently, there are more than 60 modern cell or tissue preparations for the treatment of wounds, which makes it difficult to choose the appropriate, safe and effective adjuvant therapy. A review of the world literature on the role of collagen in the process of wound healing is presented. The problems of epidemiology of chronic wounds and ulcers of various origins, physiology and pathophysiology of wound healing phases are considered. The pathogenetic role of different types of collagen, as well as the mechanisms of collagen, macrophages, fibroblasts, matrix metalloproteinases and other cytokines in the healing of ulcers are discussed.